2023
DOI: 10.1371/journal.pgph.0001855
|View full text |Cite|
|
Sign up to set email alerts
|

What interventions are effective to prevent or respond to female genital mutilation? A review of existing evidence from 2008–2020

Abstract: As the final decade of acceleration towards zero new cases of Female Genital Mutilation (FGM, SDG Target 5.3) by 2030 has begun, increasing the rigour, relevance, and utility of research for programming, policy development and resource allocation is critical. This study aimed to synthesize and assess the quality and strength of existing evidence on interventions designed to prevent or respond to FGM between 2008 and 2020.The study drew on a Rapid Evidence Assessment of the available literature on FGM intervent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 80 publications
0
2
0
Order By: Relevance
“…This is consistent with previous studies that reported the influence of media exposure on FGM practice [ 47 , 48 ]. This is because several interventions, including the National Policy and Plan of Action for the Elimination of FGM that are committed to eradicating FGM have leveraged on using the media to change the narratives of pro-FGM beliefs, opinions and perceptions [ 12 , 49 ]. Where women are exposed to such anti-FGM media campaigns, they may save their daughters from FGM, even if they themselves were mutilated.…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with previous studies that reported the influence of media exposure on FGM practice [ 47 , 48 ]. This is because several interventions, including the National Policy and Plan of Action for the Elimination of FGM that are committed to eradicating FGM have leveraged on using the media to change the narratives of pro-FGM beliefs, opinions and perceptions [ 12 , 49 ]. Where women are exposed to such anti-FGM media campaigns, they may save their daughters from FGM, even if they themselves were mutilated.…”
Section: Discussionmentioning
confidence: 99%
“…There is a dearth of knowledge regarding the effectiveness of the ARP intervention. 14 An impact evaluation study revealed that ARP played a role in increasing the years of schooling for girls and reduces the prevalence of FGM/C in Kajiado and Narok. 15 Nonetheless, the data used in this study was derived from the Demographic and Health Survey (DHS)-a secondary dataset not specifically collected for the purpose of evaluating the effectiveness of the ARP model.…”
Section: Ethics and Disseminationmentioning
confidence: 99%